La función del notario en el perfeccionamiento de tradiciones inmobiliarias - Cevallos Calero, Estefanía Corina (2025)
The function of the notary in the completion of real estate transactions in Ecuador examines the essential role of the notary in the legal security of the real estate market. As a notary public, the certifier guarantees the authenticity and legitimacy of the tradition of real estate, verifying the legal capacity of the parties and ensuring that the real estate is free of encumbrances and collecting rights. This study also analyzes how recent regulatory reforms have boosted the modernization and digitalization of the notarial system in Ecuador, improving efficiency and transparency in the management of real estate traditions. However, challenges related to cybersecurity and personal data protection persist and require urgent attention. Through a qualitative approach, the research identifies key areas for optimizing notarial functions and strengthening public trust in the legal system, promoting legal security in real estate traditions.